Development of Technology Parameter Towards Shipbuilding Productivity Predictor Using Cubic Spline Approach - Suwasono, Bagiyo; Widjaja, Sjarief; Zubaydi, Achmad; Yuliadi, Zaed; Budiantara, I Nyoman (Makara Journal of Technology, 2010)
Development of Technology Parameter Towards Shipbuilding Productivity Predictor Using Cubic Spline Approach. Ability of production processes associated with state-of-the-art technology, which allows the shipbuilding, is customized with modern equipment. It will give impact to level of productivity and competitiveness. This study proposes a nonparametric regression cubic spline approach with 1 knot, 2 knots, and 3 knots. The application programs Tibco Spotfire S+ showed that a cubic spline with 2 knots (4.25 and 4.50) gave the best result with the value of GCV = 56.21556, and R2 = 94.03%.Estimation result of cubic spline with 2 knots for the PT. Batamec shipyard = 35.61 MH/CGT, PT. Dok & Perkapalan Surabaya = 27.49 MH/CGT, PT. Karimun Sembawang Shipyard = 27.49 MH/CGT, and PT. PAL Indonesia = 19.89 MH/CGT.